2020
DOI: 10.1002/nbm.4370
|View full text |Cite
|
Sign up to set email alerts
|

3D free‐breathing cardiac magnetic resonance fingerprinting

Abstract: Purpose To develop a novel respiratory motion compensated three‐dimensional (3D) cardiac magnetic resonance fingerprinting (cMRF) approach for whole‐heart myocardial T1 and T2 mapping from a free‐breathing scan. Methods Two‐dimensional (2D) cMRF has been recently proposed for simultaneous, co‐registered T1 and T2 mapping from a breath‐hold scan; however, coverage is limited. Here we propose a novel respiratory motion compensated 3D cMRF approach for whole‐heart myocardial T1 and T2 tissue characterization from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 75 publications
4
76
0
Order By: Relevance
“…Phantom studies show that the T 1 , T 2 , and T 1⍴ maps obtained with the proposed MRF approach are comparable and in good agreement with those obtained from SE-prepared conventional scans. An excellent correlation 1,20,28,36,44 The T 1⍴ -MRF shows excellent correlation with T 1⍴ -prepared SE reference, and only a slight underestimation for MRF values was observed for high T 1⍴ values, which may be F I G U R E 3 Short-axis view of T 1 , T 2 , and T 1ρ quantitative maps in 3 representative healthy subjects. Conventional maps (top row) of T 1 -MOLLI, T 2 -GRASE, and T 1⍴ -TFE are compared with the proposed inherently co-registered T 1 , T 2 , and T 1⍴ cardiac MRF maps (bottom row) obtained from an approximate 16-second single scan caused by an insufficient encoding power provided by the SL pulse preparations for the highest T 1⍴ values.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Phantom studies show that the T 1 , T 2 , and T 1⍴ maps obtained with the proposed MRF approach are comparable and in good agreement with those obtained from SE-prepared conventional scans. An excellent correlation 1,20,28,36,44 The T 1⍴ -MRF shows excellent correlation with T 1⍴ -prepared SE reference, and only a slight underestimation for MRF values was observed for high T 1⍴ values, which may be F I G U R E 3 Short-axis view of T 1 , T 2 , and T 1ρ quantitative maps in 3 representative healthy subjects. Conventional maps (top row) of T 1 -MOLLI, T 2 -GRASE, and T 1⍴ -TFE are compared with the proposed inherently co-registered T 1 , T 2 , and T 1⍴ cardiac MRF maps (bottom row) obtained from an approximate 16-second single scan caused by an insufficient encoding power provided by the SL pulse preparations for the highest T 1⍴ values.…”
Section: Discussionmentioning
confidence: 87%
“…magnetic resonance fingerprinting, mapping cardiac MRI, multiparametric mapping, T 1⍴ as previously proposed. 28 Briefly, the following reconstruction algorithm solves the problem:…”
Section: Magnetic Resonance Fingerprinting Reconstructionmentioning
confidence: 99%
“…HD-PROST has been successfully applied to multi-contrast CMR, including accelerated free-breathing 3D high-resolution myocardial T2 [54] and T1ρ [14] mapping. HD-PROST has also been combined with LRI for cardiac MRF methods [55][56][57][58], such as water-fat Dixon cardiac MRF [58] and 3D free-breathing cardiac MRF [55], as well as free-running 3D myocardial T1/T2 mapping [24,59]. Example water-fat images and parametric maps from Dixon cardiac MRF are shown in figure 5.…”
Section: (Ii) Low-rank Tensormentioning
confidence: 99%
“…Early approaches attempted to use zero-filled reconstruction to produce the images for each time point [ 17 ], however subsequent studies demonstrated that remaining aliasing artefacts can affect the multiparametric quantification [ 27 ]. Thus, several undersampled reconstruction approaches have been proposed exploiting the temporal and spatial redundancies in the highly undersampled time series of images [ 28 , 29 , 30 ].…”
Section: The Principles Of Magnetic Resonance Fingerprintingmentioning
confidence: 99%